MODERN ASPECTS OF COMMUNITY-ACQUIRED PNEUMONIA IN PATIENTS WITH DIABETES MELLITUS - Makharynska, O. S.; Zhuravka, N. V. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine")
Clinical importance of the community-acquired pneumonia clinical course and treatment in patients with diabetes mellitus is discussed in this review. Clinical characteristics, immunological parameters, possible drugs regimen, depending on community-acquired pneumonia severity, and the ability to optimize therapy with antibacterial drugs are considered. The features of the appointment of antibacterial drugs in the step-down antibacterial therapy, peculiarities of pneumonia in patients with diabetes mellitus. Despite absence of specific guidelines for CAP treatment in patients with concomitant DM, this patients should be treated carefully because of: increased risk of infectious pathology, presence of the macro and micro complications of DM which can affect antibacterial drugs bioavailability and both diseases clinical course; pathological changes in immunity of DM patients with decreasing of immune reactivity to infectious agents; specific medication interactions between antibacterial drugs and glucose lowering agents as respiratory fluoroquinolones interactions with glucose lowering agents could lead to severe hypoglycemia; high risk of DM and CAP complication.